2018
DOI: 10.1055/a-0587-5753
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of GFR Estimation Formulae in Pediatric Oncology

Abstract: This study compares proposed pediatric GFR estimating equations in a clinical setting. It underlines the current limitations and difficulties of GFR estimation including potential dosing errors. Cystitis C-based equations can be used as alternatives to creatinine-based estimations when the appropriate laboratory method has been applied. A comparative calculator for pediatric GFR estimating equations along with background information is provided at http://gfr.pedz.de and may support clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Some meta-analyses have reported that CysC is superior to creatinine as a marker of renal function (34,35) . Cystatin C is eliminated mainly by glomerular filtration, correlates with GFR, and it is very sensitive even in mildly impaired kidney function so some studies have suggested it as an ideal GFR marker in pediatric oncology (36) . The validation of the Schwartz formula and the calculations based on serum CysC was done in several studies by comparing them to nuclear scanning methods, which suggest that they are closely correlated to GFR (37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses have reported that CysC is superior to creatinine as a marker of renal function (34,35) . Cystatin C is eliminated mainly by glomerular filtration, correlates with GFR, and it is very sensitive even in mildly impaired kidney function so some studies have suggested it as an ideal GFR marker in pediatric oncology (36) . The validation of the Schwartz formula and the calculations based on serum CysC was done in several studies by comparing them to nuclear scanning methods, which suggest that they are closely correlated to GFR (37)(38)(39) .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise the CysC-based GFR calculation using Chronic Kidney Disease Epidemiology Collaboration GFR calculation with age 2012 (CKD-EPI) GFR Eq. ( 2012), which is an excellent and reliable way to assess renal function in pediatric patients [23,[25][26][27].…”
Section: Biological Parametersmentioning
confidence: 99%
“…2,7 Glomerular filtration rate (GFR) is best marker for assessment of renal function and its decrease correlate with loss of function of nephrons and degree of kidney failure. 8,9 For measurement of GFR commonly used methods are inulin clearance, EDTA clearance and iohexol and 24hour creatinine clearance (Ccrl). 10 Glomerular filtration rate assessment by inulin, EDTA clearance and iohexol is cumbersome and is not routinely done in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…24hours Crcl requires 24hours urine collection which is also not feasible especially in young children for routine use of GFR measurement. 8 Glomerular filtration rate estimation (eGFR) formulae have been developed for assessment of kidney function and there are variety of GFR formulas available for clinical use. eGFR formulas based on serum creatinine have been used since long and are most commonly employed for GFR monitoring at bed side among which most commonly used is Schwartz formula.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation